FEATURES OF DECOMPRESSION OF THE BILIARY TRACT IN PATIENTS WITH OBTURATION OF THE DISTAL PART OF THE COMMON BILE DUCT OF TUMOR ORIGIN - M.P. Shevchuk; M.O. Dudchenko; M.I. Kravtsiv; D.M. Ivashchenko; R.A. Prykhidko; S.M. Zaiets (Проблеми екології та медицини)
We conducted a retrospective and prospective analysis of the examination and treatment of 89 patients with cancer of the hepato-pancreato-duodenal zone complicated by mechanical jaundice. Cancer of the head of the pancreas was found in 69 patients, cancer of the major duodenal papilla was detected in 10 patients, cancer of the extrahepatic bile ducts – in 9 patients, and cancer of the duodenum – in 1 case. All patients were divided into 3 groups depending on the degree of jaundice. Operative treatment was performed in 86 patients. Of them, 13 were operated on at the height of jaundice, and 73 – after previous minimally invasive decompression of the biliary system. Postoperative complications were observed in 17 (19.1%) patients, 12 (16.4%) of whom were operated on at the height of jaundice, and 5 (6.8%) – after previous biliary decompression (second-stage operations). In 6 patients with severe jaundice who were operated on at the height of jaundice, complications occurred even after minor palliative operations. Thus, in the presence of severe jaundice with bilirubin level > 200 μmol/l, radical and palliative operations should be performed only in two stages, after preliminary decompression of the bile ducts. Decompression of the bile ducts allows the reduction of the preoperative period by 2–3 weeks.